Pengembangan Indeks Penilaian Bank Sampah Skala Kota Studi Kasus Kota Bandung dan Kota Cimahi - PRANADITYA, MEGA; JUWANA, IWAN; AINUN, SITI (Institut Teknologi Nasional, Bandung, 2020)
AbstrakBank sampah skala kota adalah aplikasi pengelolaan sampah untuk mengurangi sampah suatu kota yang akan dibuang ke TPA. Penelitian ini bertujuan untuk menyempurnakan indeks sebelumnya. Dengan meninjau indikator sebelumnya melalui tinjauan pustaka, yang kemudian akan divalidasi dengan metode AHP untuk menentukan pembobotan. Terdapat 4 kategori responden yaitu, professional expert, akademisi, instansi dan pihak bank sampah. Kajian ini menghasilkan tiga komponen, tiga belas indikator dan enam puluh satu sub-indikator teridentifikasi. Berdasarkan hasil AHP, bobot dari masing-masing komponen adalah Sistem Manajemen (40%), Sistem Operasional Â (30%) dan Fasilitas Bank Sampah (30%). Jumlah indikator dari masing-masing komponen berkisar 4-5 indikator dengan bobot 15%-35%. Adapun sub indikator memiliki jumlah berkisar 2-8 dengan bobot 10%-50%. Â Kata Kunci : Bank Sampah, Indeks, Metode AHP, Komponen, Indikator, Sub-IndikatorAbstractWaste bank is one application of waste management by utilizing waste that is considered having re-sellvalues, which at the end can be used to reduce the waste dumped into landfill. Thus, a tool to assess the readiness of a waste bank to function at a city-scale is needed.This study aims to refine the previous index. This was done by first, reviewing previous indicator through literature review, which was then verified by the application of the AHP method which was usedwas also used to determine the weights for each indicator. The respondents for AHP applications were selected from four categories which were garbage expert, academics, intitutions and management representatives of waste bank. At the end of the study, three components, thirteen indicators and sixty one sub-indicators were identified. The name of the components and their respective weights are Management System (55%), Operating System (25%) and Waste Bank Facility (20%). The number of indicators from each components ranged from 4 to 5 indicators with the weights range from 15% to 35%. As for the sub indicators, they range from 2 to 8 sub indicators with the weights between 10% to 50%. Â Kata Kunci : Waste Bank, Index, AHP Method, Components, Indicators, Sub-Indicators